Profiling patent compounds in lipid nanoparticle formulations of siRNA - Yunfeng Han; Mengyang Wang; Yu Chen; Defang Ouyang; Ying Zheng; Yuanjia Hu (Elsevier, 2024)
Lipid nanoparticles (LNPs) have emerged as a prominent delivery system for nucleic acid drugs, attracting significant attention, especially through the successful development of several commercial products. As a key component in LNPs, cationic lipids have long served as a key technical barrier to block competitors by building up a complex patent thicket. However, there have been few studies as yet that have comprehensively analyzed the patented compounds in LNP formulations, despite a large number of technical reviews and original articles. In this context, this study focuses on analyzing the macroscopic landscapes and microscopic molecular characteristics of LNP patents, aiming to provide a valuable reference for researchers and developers in making informed technological and commercial decisions. By mining 2,994 patents, 265 formulas, 7,674 compounds, and 28,789 fragments, this work sketches the empirical golden ratio of lipid materials in LNP formulation, discloses the advanced technology in the formulation, characterizes high-frequency fragments of heads, linkers and tails in both novel cationic lipids as well as targeting lipids, and establishes a virtual focus library of LNP materials.